Interplay of structural chirality, electron spin and topological orbital in chiral molecular spin valves - Adhikari, Yuwaraj; Liu, Tianhan; Wang, Hailong; Hua, Zhenqi; Liu, Haoyang; Lochner, Eric; Schlottmann, Pedro; Yan, Binghai; Zhao, Jianhua; Xiong, Peng (Nature communications, 2023)
Chirality has been a property of central importance in physics, chemistry and biology for more than a century. Recently, electrons were found to become spin polarized after transmitting through chiral molecules, crystals, and their hybrids. This phenomenon, called chirality-induced spin selectivity (CISS), presents broad application potentials and far-reaching fundamental implications involving intricate interplays among structural chirality, topological states, and electronic spin and orbitals. However, the microscopic picture of how chiral geometry influences electronic spin remains elusive, given the negligible spin-orbit coupling (SOC) in organic molecules. In this work, we address this issue via a direct comparison of magnetoconductance (MC) measurements on magnetic semiconductor-based chiral molecular spin valves with normal metal electrodes of contrasting SOC strengths. The experiment reveals that a heavy-metal electrode provides SOC to convert the orbital polarization induced by the chiral molecular structure to spin polarization. Our results illustrate the essential role of SOC in the metal electrode for the CISS spin valve effect. A tunneling model with a magnetochiral modulation of the potential barrier is shown to quantitatively account for the unusual transport behavior. Chirality induced spin selectivity is a process whereby a chiral molecule induces a spin-polarization to a current passing along the chiral molecule. The exact physical origin of the effect is still debated despite extensive experimental result. Here, Adhikari et al provide evidence for the important role of spin-orbit coupling in the normal metals that connect to the chiral molecule in CISS experiments.